Protecting children from domestic violence: strategies for community intervention - Jaffe, Peter G. (Guilford Press, 2004)
Part I: Introduction to the problem -- Purpose and overview / Peter G. Jaffe, Linda L. Baker, and Alison J. Cunningham -- Should childhood exposure to adult domestic violence be defined as child maltreatment under the law? / Jeffrey L. Edleson -- Young children exposed to adult domestic violence: incidence, assessment, and intervention / B. B. Robbie Rossman, Jacqueline G. Rea, Sandra A. Graham-Bermann, and Perry M. Butterfield -- Group intervention with abusive male adolescents / Diane Davis -- Part II: Individual- and group-level responses -- Fostering resilient coping in children exposed to violence: cultural considerations / Sandra A. Graham-Bermann and Hilda M. Halabu -- Safety planning for abused women and their children / Jennifer L. Hardest and Jacquelyn C. Campbell -- Assessing abusers risks to children / Lundy Bancroft and Jay G. Silverman -- Fatherhood and domestic violence: exploring the role of abusive men in the lives of their children / Oliver J. Williams, Jacquelyn Boggess, and Janet Carter -- Part III: System-level responses -- The ethnic media outreach project: Canada is a country for women / Melpa Kamateros -- Police in the lives of children exposed to domestic violence: collaborative approaches to intervention / Miriam Berkman, Robert L. Casey, Steven J. Berkowitz, and Steven Marans -- The role of family courts in domestic violence: the Canadian experience / Martha Shaffer and Nicholas Bala -- The role of family courts in domestic violence: the U.S. experience / Billie Lee Dunford-Jackson -- The fourth R: developing healthy relationships through school-based interventions / Peter G. Jaffe, David Wolfe, Claire Crooks, Ray Hughes, and Linda L. Baker -- Part IV: Conclusions -- Future directions in ending domestic violence in the lives of children / Linda L. Baker, Alison J. Cunningham, and Peter G. Jaffe